2003
DOI: 10.1159/000072428
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sialidase from an Influenza A (H3N2) Virus Strain: Kinetic Parameters and Substrate Specificity

Abstract: Neuraminidase (NA) of influenza A (H3N2) viruses was characterized after purification by gel filtration and proteolytic treatment, using the X-31 variant strain that is a reassortment between the influenza A/Victoria/3/75 (responsible for the 1975 pandemic) and the influenza A/PR/8/34 virus samples, as a model. In the purification process, NA heads, that is the spike responsible for the virus sialidase activity, were purified by filtration through a Bio-Gel polyacrylamide column. The enzyme activity was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…All of these results imply that the N1 enzyme of the avian influenza virus binds in the binding mode that facilitates preferential cleavage of sialic acid from methyl 3"sialyllactoside over methyl 6"sialyllactoside. These results are consistent with experimental data that showed that avian influenza virus desialylates α-Neu5Ac-2,3-linked oligosaccharides at least one order faster than α-Neu5Ac-2,6-linked oligosaccharides [6] and with the data on specificity of the human influenza virus neuraminidases [4,5].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 91%
See 2 more Smart Citations
“…All of these results imply that the N1 enzyme of the avian influenza virus binds in the binding mode that facilitates preferential cleavage of sialic acid from methyl 3"sialyllactoside over methyl 6"sialyllactoside. These results are consistent with experimental data that showed that avian influenza virus desialylates α-Neu5Ac-2,3-linked oligosaccharides at least one order faster than α-Neu5Ac-2,6-linked oligosaccharides [6] and with the data on specificity of the human influenza virus neuraminidases [4,5].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 91%
“…In contrast to hemagglutinin, there is only limited information on neuraminidase substrate specificity, though it has been suggested that neuraminidase preferentially recognizes the same linkage of sialic acid as the hemagglutinin of these viruses [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drzeniek found that early H2N2 strains cleaved 3’SiaLac about 10-fold faster than fetuin or ovomucoid, and 20 times faster than orosomucoid (α1 acid glycoprotein), Tamm-Horsfall protein from urine, or porcine submaxillary mucin 53 . A similar gradient from 3’SiaLac to fetuin to bovine mucin was found for A/Aichi/68 (H3N2) NA 54 . The extensive O-acetylation of mucin contributes to its low activity as substrate; 4-O-acetylSia is not cleaved at all, while sialic acids with O-acetyl groups at 7, 8 or 9 positions on the glycerol chain are cleaved slowly 55 .…”
Section: Substrate Specificitysupporting
confidence: 72%
“…The strength of the substrate binding is in the following order: 3SL > 6SL >> sialic acid. This might be a reason that an avian N1 was experimentally found to cleave the SA-α-2,3-Gal glycoconjugates better than the SA-α-2,6-Gal [27][28][29] .…”
Section: Neuraminidasementioning
confidence: 99%